Deadpool. Vol. 3, Revenge of Wade Wilson - Ziglar, Cody (Marvel Worldwide, a subsidiary of Marvel Entertainment, 2025)
Deadpool is back from the dead, and he's out for revenge - in the action-packed, wacky that he does best! Death Grip killed Deadpool. Then Wade Wilson got better. Now he's out to return the favor, armed with a deadly new weapon! His first stop is Solem, the mutant who armed Mr. Grip with the Muramasa Blade that did him in. It's karma time! Fighting side-by-side with his daughter, Ellie, Wade takes the fight to the cult of Death Grip -- but even in death, it seems their diabolical leader keeps a tight hold on them! So now Wade and Ellie must face hordes of undead mystics! That's the job, Deadpools! COLLECTING: Deadpool (2024) 13-15.